Characterization of Phytochrome-Interacting Factor Genes in Pepper and Functional Analysis of CaPIF8 in Cold and Salt Stress - Yang, Youxin; Guang, Yelan; Wang, Feng; Chen, Yue; Yang, Wenting; Xiao, Xufeng; Luo, Sha; Zhou, Yong (Frontiers in Plant Science, 2021)
As a subfamily of basic helix-loop-helix (bHLH) transcription factors, phytochrome-interacting factors (PIFs) participate in regulating light-dependent growth and development of plants. However, limited information is available about PIFs in pepper. In the current study, we identified six pepper PIF genes using bioinformatics-based methods. Phylogenetic analysis revealed that the PIFs from pepper and some other plants could be divided into three distinct groups. Motif analysis revealed the presence of many conserved motifs, which is consistent with the classification of PIF proteins. Gene structure analysis suggested that the CaPIF genes have 5 to 7 introns, exhibiting a relatively more stable intron number than other plants such as rice, maize and tomato. Expression analysis showed that CaPIF8 was up-regulated under cold and salt treatments. CaPIF8-silenced pepper plants obtained by virus-induced gene silencing (VIGS) exhibited higher sensitivity to cold and salt stress, with an obvious increase in relative electrolyte leakage (REL) and variations in the expression of stress-related genes. Further stress tolerance assays revealed that CaPIF8 plays different regulatory roles in cold and salt stress response by promoting the expression of the CBF1 gene and ABA biosynthesis genes, respectively. Our results reveal the key roles of CaPIF8 in cold and salt tolerance of pepper, and lay a solid foundation for clarifying the biological roles of PIFs in pepper and other plants.